Virus Injection to the Pituitary via Transsphenoidal Approach and the Innervation of Anterior and Posterior Pituitary of Rat - Li, Xiaohui; Su, Shanchun; Zhao, Haiwen; Li, Yang; Xu, Xueqin; Gao, Yan; Sun, Dongsheng; Yang, Zeyong; Jin, Weilin; Ke, Changbin (Frontiers in Endocrinology, 2020)
The theory holds that the anterior pituitary of mammalian receives humoral regulation. Previous researches reported that there were substance P-, calcitonin gene-related peptide (CGRP)-, and galanin-like immunoreactive nerve fibers in the pars distalis of anterior pituitary of several mammalian species. The origin of these nerve fibers of mammalian anterior pituitary is unclear. Methods to remove the pituitary gland, also called hypophysectomy, are via stereotaxic, transauricular or parapharyngeal pathway. These methods are not suitable for viral tracer injection to investigate the innervation of anterior pituitary. Stereotaxic and transauricular methods lead to inaccurate pituitary localization. Parapharyngeal approach causes higher mortality in animals. Here, we introduce a protocol that exposes the pituitary gland of rat through transsphenoidal pathway imitating surgical manipulations, such as endotracheal intubation and sphenoid bone drilling, with the operation of self-made devices. The method greatly improves the survival rate of rats because it reduces the damage of blood vessels and nerves without additional dissection. Moreover, the pituitary gland can be operated under a clear vision, so it is suitable for accurate injection pseudorabies virus (PRV) 152 expressing enhanced green fluorescent protein (EGFP) into the anterior pituitary or posterior pituitary, respectively. The results show that there is no direct innervation of the anterior pituitary in brain when PRV 152 injected into the anterior pituitary of rat. Retrograde transneuronal cell body infections in many areas of the brain, such as field CA1 of hippocampus, basolateral amygdaloid nucleus, posterior part (BLP), arcuate hypothalamic nucleus (Arc), dorsomedial hypothalamic nucleus, dorsal part (DMD), suprachiasmatic nucleus (SCh) and subfornical organ (SFO) were identified after PRV 152 injected into the posterior pituitary. In the present study, we provide a recipe for a possible model of hypophysectomy or pituitary injection, as well as to identify central nervous systerm brain regions which regulate the rat pituitary by transneuronal retrograde cell body labeling with PRV.